(untitled) (Revista NUPEART, 2024)
This study aims to reflect on the formation of the master of popular culture Agenor Abreu as a musician and his teaching performance. The data collection instrument used here consists of semi-structured interviews conducted with the master. The theoretical perspective is based on Cascudo’s (2005) folklore concepts and formal, non-formal, and informal learning from Libâneo (2010) and Gohn (2010). It was possible to understand that Agenor began to learn music informally in childhood and in adulthood had contact with the formal teaching of this art. In his teaching performance, he sought to work with the traditional repertoire of his home state, however, with a different approach from that employed by popular musicians from the interior. Finally, it is concluded that popular culture masters, such as Agenor, carry with them a portion of the knowledge of their regions and without adequate registration, this knowledge can be lost.